Difficulties in diagnosis and treatment of Paget’s disease - Kawalec, Aleksandra; Zdrojowy-Wełna, Aleksandra; Bednarek-Tupikowska, Grażyna (Family Medicine & Primary Care Review, 2016)
Paget’s disease is a rare finding in Poland. It is a disorder of the osteoarticular system, which, in adults, mostly affects people over 55 years of age. The clinical picture varies, depending on the location of the lesions, making the diagnosis difficult, sometimes taking many years for a correct diagnosis to be made. In etiopathogenesis, genetic predispositions as well as viral infections play an important role. From the genetic point of view, Paget’s disease is heterogeneous, as numerous mutations are known, and the genotype to phenotype relationship is unclear. The first phase of the disease is characterized by an increased osteocytes activity, due to morphologically changed and RANKL overstimulated osteocytes. This leads to an intensification of ossification processes that occur in a chaotic manner. Therefore, the resulting bone is weak, extensively vascularized and there is an increased risk of fracture or deformity. Clinical manifestations of Paget’s disease might include pain, excessive warmth, bone deformations, degenerative lesions in the adjacent joints, compression of the neural structures, hearing loss, and dilated cardiomiopathy. Other possible complications include the development of benign and malignant bone tumors and hypercalcaemia in the case of immobilization. An elevated level of serum alkaline phosphatase, bone x-ray and bone scintigraphy are crucial in making the diagnosis. The disease should be distinguished from osteomalacia, osteoporosis, hyperparathyroidism and multiple myeloma. Bisphosphonates at doses higher than those applied for osteoporosis are an effective treatment. The occurrence of orthopedic, neurological and laryngological complications is often a reason for surgical intervention.